Patterns of vasopressor utilization during the resuscitation of massively transfused trauma patients. Issue 1 (January 2018) - Barmparas, Galinos; Dhillon, Navpreet K.; Smith, Eric JT; Mason, Russell; Melo, Nicolas; Thomsen, Gretchen M.; Margulies, Daniel R.; Ley, Eric J.
Abstract: Background: The use of vasopressors (VP) in the resuscitation of massively transfused trauma patients might be considered a marker of inadequate resuscitation. We sought to characterize the utilization of VP in patients receiving massive transfusion and examine the association of their use with mortality. Methods: Trauma patients admitted from January 2011 to October 2016 receiving massive transfusion, defined as 3 units of pRBC within the first hour from admission, were selected for analysis. Demographics, admission vital signs and labs, use of VP, surgical interventions and outcomes were collected. Standard statistical tools were utilized. Results: Over the 5-year study period, 120 trauma patients met inclusion criteria. The median age was 39 years with 77% being male and 41% sustaining a penetrating injury. Patients who received VP [VP (+)] were more likely to have a lower admission GCS (median 4.5 vs. 14.0, p < 0.01) and less likely to have a penetrating injury (31% vs. 54%, p = 0.02). The overall mortality was 49% and significantly higher in the VP (+) cohort (60% vs. 34%, AHR: 9.9, adjusted p = 0.03). Mortality increased in a stepwise fashion with increasing number of VP utilized, starting at 34% for no VP, to 78% for 3 VP, and 100% for 5 or more. The majority of deaths in the VP (−) group (88%) occurred within one day from admission. For the VP (+) group, 57% of deaths occurred within one day, with the remaining 43% occurring at a later time. Conclusion: In the era of massive transfusion protocols, vasopressors are commonly utilized in exsanguinating trauma patients and their use is associated with a higher mortality risk. Deaths in patients receiving vasopressors are more likely to occur later compared to those in patients who do not receive vasopressors. Further research to characterize the role of these agents in the resuscitation of trauma patients is required.